Demokrasi di Desa (Studi Kasus Pemilihan Kepala Desa Batu Timbau Kabupaten Kutai Timur): Democracy in the Village [Study Case of Village Head Election of Batu Timbau, East Kutai District] - Budiman; Jauchar B; Anwar Alaydrus; Jemi Aminurosyah (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2021)
This research examines rural democratic system in the election of Village Head of Batu Timbau by involving adat (customary) institution. In data collection, this research used interviews, as well as observation, and documentation; and in analyzing data, a descriptive qualitative method was employed. The study concludes that any candidate should be a member of customary community and hold a recommendation from village customary institution. This rule was made based on the agreement among village government, customary institution, and community leader aiming at preserving cultural heritage, customary land, and customary rights. In fact, the elected village government of Batu Timbau has adopted rural democractic system with adat characteristics